Durabilidade da madeira de quatro espécies de eucaliptos submetidas a testes de campo. - Delucis, Rafael de Ávila (2014)
This study aimed to characterize the deterioration of juvenile and mature of four species of eucalypts wood subjected to three different field tests. The study material consisted of adult trees of the species Eucalyptus botryoides, Corymbia citriodora, Eucalyptus paniculataand Eucalyptus tereticornis, which were randomly selected in the Charqueadas city, Rio Grande do Sul state. After the overthrow, from the each basal log with 1,5 m length, were cut samples with dimensionsof 1 cm x 1 cm x 20 cm (larger in the axial direction) taken in the regions near the pith and bark of trees in order to characterize the selection of juvenile and mature wood, respectively. To evaluate the durability of the material, three decaying fields were installed in different microclimates in Piratini city, Rio Grande do Sul state. Exposureenvironments were referred to as: outdoor field, flooded field and forest field. The material was characterized as biodeterioration through physical (weight loss, specific gravity and equilibrium moisture content), colorimetric (CIEL*a*b*method), mechanical (flexural) and visual (assignment notes because of plant health) parameters. As to natural weathering, the surface of the samples from the outdoor field were characterized by means of color parameters (CIEL*a*b*method and UV-VIS spectroscopy), the surface wettability (contact angle analysis) and surface hardness (Janka method). Fromthe point of view of biodegradation, the mass loss was the major classification parameter of wood, however, other characterization techniques contributed additional interesting results. It was found that the samples tested in the field plated had higher microbial activity, causing major damage in this properties. As to natural weathering, we highlight the Janka Hardness as a parameter for comparisons between different wood species and this juvenile and mature woods. The mature wood of all species showedgreater durability than juvenile wood as much as biodeterioration, and as the natural weathering. In general, it appears that the Corymbia citriodoraand Eucalyptus tereticorniswood showed the highest natural indices of the spoilage agents, so they aresuitable for the manufacture of solid products for external use.